Phase evolution of NiTiO3 prepared by coprecipitation method - Murugan, A. Vadivel; Samuel, V.; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A simple coprecipitation technique was used for the preparation of NiTiO3 powders. Ammonium carbonate solution was added to a solution mixture containing stoichiometric amounts of Ni(NO3)(2) and TiOCl2 to precipitate nickel as carbonate and titanium as hydroxide under basic conditions. The precipitate was calcined at different temperatures ranging from 100 to 800 degrees C and phase evolution of NiTiO3 was investigated by X-ray diffraction (XRD) studies. It is observed that nickel titanate was formed at 750 degrees C. For comparison, NiTiO3 was also prepared by standard ceramic process. Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All fights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; NiTiO3; Oxides; X-ray diffraction

Co-precipitation technique to prepare BaTa2O6 - Navale, S. C.; Samuel, Violet; Gaikwad, A. B.; Ravi, V. (Ceramics International, 2007)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate barium and tantalum ions as barium oxalate and tantalum hydroxide under basic conditions. On calcination at 750 degrees C, this precursor yielded BaTa2O6 (BT) ceramics. This is much lower temperature as compared to that prepared by traditional solid-state method (1000 degrees C) as reported for the formation of BaTa206. Transmission electron microscope (TEM) investigations revealed that the average particle size is 70 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 100. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: barium tantalate; Ceramics; Electron microscopy; Oxides; X-ray diffraction

Varistors based on Ta-doped TiO2 - Navale, S. C.; Murugan, A. Vadivel; Ravi, V. (Ceramics International, 2007)
The nonlinear current (I)-voltage (V) characteristics of titanium dioxide are examined when doped with small quantities (0.05-0.5 at.%) of tantalum pentaoxide. For optimum compositions, the nonlinear coefficients are found to be in the range of 25-30 and the breakdown field strength (EB) is similar to 4000 V/cm. The obtained alpha- and E-B-values are higher than the previously reported values for TiO2 ceramics. The acceptor like surface states at the grain boundary adsorb oxygen during sintering and cooling, leading to formation of grain boundary barrier. The grain boundary barrier height (OB) is calculated using Schottky equation. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Oxides; Schottky barrier; TiO2; varistor